Relevansi Pendidikan Perspektif Al-Ghazali Terhadap Paradigma Pendidikan Islam di Indonesia - Sef, Widad; Abu Bakar, M. Yunus (UIR Press, 2024)
Education often experiences challenges and developments that continue to occur according to changing times, so it is very important to prepare educators to have the ability to adapt to the transformation of science and technology to develop the potential of students in the future. This research is a type of descriptive qualitative research that refers to historical-factual philosophical research regarding figures with the object of research being the thoughts of a philosopher, using library research techniques. The results of this research is Al-Ghazali has listed several aspects of education, including: educational goals, characteristics that educators and students must have, educational curriculum, and learning methods. Al-Ghazali's thoughts have relevance to Islamic education in Indonesia in terms of educational goals, the importance of the role of educators towards students, apart from that the curriculum classifies fields of knowledge based on the needs and abilities of students. The learning method introduced by Imam Al-Ghazali is considered relevant to the context of Islamic education in Indonesia, considering the diversity of nations with different characteristics and backgrounds. So Al-Ghazali's thoughts regarding the concept of education are quite relevant to use, this can be implemented in Islamic education patterns in Indonesia and can be an inspiration and answer several challenges that arise in the world of education.